2008
DOI: 10.1002/jhm.281
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum cardiomyopathy presenting as splenic infarct

Abstract: A 26-year-old woman presented with a 1-week history of epigastric and left upper quadrant pain associated with nausea and vomiting. She also described 3 weeks of constant substernal chest pain, dyspnea, and decreased exercise tolerance.Her medical history was significant for a pituitary macroadenoma diagnosed 6 years previously that had been treated with cabergoline. She had a miscarriage 7 years ago but gave birth to a healthy child 5 months prior to admission. She had smoked 2 cigarettes per day for the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Although acute pulmonary artery thromboembolism was not reported in these 6 cases, it may develop in patients with PPCM and RV thrombus. In PPCM, embolism to cerebral artery, coronary artery, splenic artery, and artery of lower extremity has been reported [21][22][23][24]. Amos et al reported that in 55 patients, the incidence of LV thrombus complicating PPCM was 17%, and only one patient suffered thromboembolism (coronary artery thromboembolism) [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although acute pulmonary artery thromboembolism was not reported in these 6 cases, it may develop in patients with PPCM and RV thrombus. In PPCM, embolism to cerebral artery, coronary artery, splenic artery, and artery of lower extremity has been reported [21][22][23][24]. Amos et al reported that in 55 patients, the incidence of LV thrombus complicating PPCM was 17%, and only one patient suffered thromboembolism (coronary artery thromboembolism) [14].…”
Section: Discussionmentioning
confidence: 99%
“…59 Less commonly, PPCM manifests with cardiogenic shock requiring mechanical or inotropic circulatory support or symptomatic or even unstable arrhythmias 60 , 61 and coronary artery thrombosis. 62 …”
Section: Methodsmentioning
confidence: 99%
“…Less commonly, women present with cardiogenic shock that requires inotropic or mechanical circulatory support. Uncommon presentations include symptomatic or even unstable arrhythmias7172 and arterial thromboembolism 7374. Most women present postpartum, mainly during the first month after delivery; a considerable number present in the late antepartum period; and rare cases present as early as the second trimester 66375.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Thrombosis may occur in both left sided and right sided cardiac chambers 7374101102103104105106107108. Mechanisms underlying intracardiac thrombosis in PPCM include cardiac dilatation and hypocontractability leading to blood stasis, as well as endothelial injury 13.…”
Section: Natural Course and Prognosismentioning
confidence: 99%